DEVELOPMENT AND PERFORMANCE ANALYSIS OF AN IOT- ENHANCED SMART VERTICAL FARMING SYSTEM FOR SUSTAINABLE URBAN AGRICULTURE - Faiq Said,; Muhammad Azhar,; Sajid Khan,; Sahibzada Naveed Inayat Ullah,; Farhan Ali,; Muhammad Ayub Khan, (Spectrum of Engineering Sciences, 2025)
This study presents the design, fabrication, and performance evaluation of an advanced IoT-integrated domestic vertical farming system, combining hydroponics and automation to achieve optimal efficiency in urban agriculture. The system incorporates a 12V, 15W pump with a flow rate of 10 L/min and a pressure head of 2.10 m, operating at 4.22 W with an efficiency of 78%, ensuring minimal energy consumption while maintaining effective irrigation. The ESP32/Node MCU microcontroller-controlled temperature, humidity, water level, and total dissolved solids (TDS) sensors used in IoT-enabled monitoring showed remarkable accuracy, with sensor accuracy variances of ±2% for water and nutrient levels and ±3% for temperature and humidity. A consistent temperature of 34.2°C and humidity of 43% were recorded by real-time monitoring, and a quick reaction time of less than five seconds was guaranteed by automated irrigation and nutrient delivery. By providing a user-friendly interface for remote control and real-time data presentation, the Arduino Cloud dashboard improves system usability. Because it is affordable and scalable, its remarkable vertical farming performance which includes improved resource use, less manual labor, and enhanced crop growth makes it a great choice for sustainable urban agriculture.